Effects of Utilizing Physics Podcasts on the ICT Literacy Skills of Grade 9 Junior High School Students - Millanes, Ma. Angelie A.; Paderna, Edwehna Elinore S.; Que, Elenita N. (Alipato, A Journal of Basic Education, 2018)
In this current educational landscape, educators are being challenged to look for innovative ways to teach and integrate various literacy skills essential for the 21st century. As a form of Information and Communications Technology (ICT) tools, podcasting is now an emerging trend in pedagogy because it offers an alternative means of delivering content and enhances the learning and skills of today’s learners. To verify this, the study aimed to determine whether the integration of 13 podcasts episodes as supplementary instructional materials in teaching different physics concepts could yield significant and positive increase on the level of ICT literacy skills among the students. It utilized an experimental pretest-posttest one-group design involving Grade 9 junior high school students from a laboratory school in Laguna, Philippines. A researcher-made instrument called ICT Literacy Skills Inventory (ICTLSI) was administered to the research sample in order to measure the impact of this teaching strategy on student ICT literacy skills, particularly on the following proficiencies: (1) Define, (2) Access, (3) Manage, (4) Integrate, (5) Evaluate, (6) Create, and (7) Communicate. Results showed that there was a positive increment in the pretest and posttest mean scores of the students after the intervention. Furthermore, four out of the seven proficiencies – Define, Access, Evaluate, and Create exhibited a result with significant improvement. It was found out that podcasting is pedagogically powerful in enhancing the level of ICT literacy skills among the students since it provides advantages to complement traditional curriculum delivery. Keywords: Information and Communications Technology (ICT) literacy skills, instructional material, physics education, podcast